THE INFLUENCE OF MOTIVATION ON THE PERFORMANCE OF NON-PERMANENT EMPLOYEES (PTT) IN THE PUBLIC PRAJA POLICE UNIT, PASER REGENCY - Sadhono, Agus Budi; Susanti, Erni; Halid, Ahmad (Universitas Gajah Putih, 2020)
PTT's role in improving management functions is the obligation of every leader to encourage and motivate each of his subordinates. While currently at the Civil Service Police Unit Service, Paser Regency, for Non-Permanent Employees or abbreviated as PTT, the fulfillment of PTT needs is still not optimal. The type of research used in this research is quantitative research with a quantitative descriptive approach. The population in this study were all PTT at the Civil Service Police Unit Service, Paser Regency, totaling 90 people. In this study, all the numbers in the population were 90 respondents Data collection techniques are the main steps in a research, because from collecting this data the goal of a research can be achieved, namely to obtain data. Without data collection techniques, you will not be able to obtain the data you want and need in a study. Data collection techniques used were observation, interviews and questionnaires. Qualitative data analysis is inductive in nature, namely an analysis based on the data obtained, then a certain relationship pattern is developed or a hypothesis is developed. In researching and analyzing and testing hypotheses in this study, the researchers used multiple linear regression, multiple correlation analysis of correlation coefficient (R), Coefficient of Determination (R2), F test and t test. Multiple linear regression is basically an extension of simple linear regression, namely increasing the number of independent variables that were previously only one to become two or more independent variables. The value of the correlation coefficient (R) is 0.914 which means the relationship between the independent variable and the dependent variable is very strong because it is at the level of 0.80-1.000